2007
DOI: 10.33762/mjbu.2007.48779
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidiosis and Immunological Status in Children With Malignant Diseases

Abstract: Objective: To investigate the relationship of Cryptosporidium and immunological parameters among children with malignant diseases. Methods: Stool samples were collected from 101 children with malignant disease and 107 apparently healthy children. Direct smear method and then formalin-ether sedimentation method were done for all stool samples to identify intestinal parasites. Fecal smears were prepared from the sediment and stained by the modified Ziehl-Neelsen method for the recovery of acid-fast oocysts of Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
1
0
1
Order By: Relevance
“…A study in Addis Ababa, Ethiopia showed infection with the microsporidia parasite using PCR method, the results were 39(16%) positive out of 243 stool samples. This study in slightly disagreed with present study regarding the rate of infection with microsporidia (11).…”
Section: Discussioncontrasting
confidence: 99%
“…A study in Addis Ababa, Ethiopia showed infection with the microsporidia parasite using PCR method, the results were 39(16%) positive out of 243 stool samples. This study in slightly disagreed with present study regarding the rate of infection with microsporidia (11).…”
Section: Discussioncontrasting
confidence: 99%
“…The highest percentage of protozoal infection was recorded among patients with lymphoma (77.27%) followed by (62.26%) among patients with leukemia and (40%) among patients with solid tumors, this difference was not significant (p > 0.05) (Table 3). These results were similar to that of Mahdi et al who reported infection rates of 60.86%, 46.66%, and 44.44% among patients with lymphoma, leukemia, and solid tumors respectively (20). The higher incidence rate of enteric protozoal infections among patients with lymphohematopoietic malignancies could be due to their effects on immunity mechanisms that include mucosal membrane, skin, quantitative and qualitative defect of granulocytes and macrophages (21).…”
Section: Resultssupporting
confidence: 88%